Science Teachers ’ Beliefs and the Epistemological Underpinnings of the Science Curriculum for Secondary Education in Tanzania - Tarmo, Albert Paulo (Papers in Education and Development, 2020)
This study intended to establish why science teachers in Tanzania are quick in discarding learner-centred pedagogic practices in favour of the default transmissive teaching. The study explored science teachers ' beliefs about knowledge and analysed science curriculum to establish its ' epistemological underpinnings. Afterward, the study compared science teachers ' beliefs with the epistemological foundations of the curriculum to establish the (in) congruity between the two. It was found that science teachers held beliefs about scientific knowledge that largely contrast the assumptions about knowledge that underlie secondary science curriculum in Tanzania. It was concluded that science teachers in Tanzania could be resisting pedagogical change partly because the basic assumptions about scientific knowledge associated with learner-centred pedagogy as reflected in the curriculum are inconsistent with those they hold. Keywords: pedagogy, learner-centred pedagogy, epistemic belief, nature of science.